STRATEGI KOMUNIKASI BISNIS DALAM MENINGKATKAN KEPUASAN TENANT - Ary Mulyani Putri; Poppy Ruliana (Inter Script : Journal of Creative Communication, 2019)
The problem in this study is the Grand Tarakan Mall, which is the only Modern shopping center in the Tarakan area, must intensify its promotion in increasing customer satisfaction to work together by developing the right Business Communication Strategy in its implementation, so that customer satisfaction can be achieved. This study aims to look at the Business Communication Strategy in Increasing Customer Satisfaction conducted by Grand Tarakan Mall and this study focuses on promotions promoted by Grand Tarakan Mall. The concept used in this study is the S7 Pillar Theory of Communication Strategy by Cutlip & Center (1952) and Kotler's Customer Satisfaction Analysis Theory. And PLC by Kotler (1991). The research subjects were the management of GTM marketing, with 1 key informant and 2 other informants, and used a qualitative approach. The methode used in this research is descriptive qualitatif method. with the source of information informan key GTM president Directur and two GTM operational Directur informan and Directur of marketing XX1. Data collection technic used to obsevation, interview guidelines, indeepth interview, preier and secondary data and documentation studi. While technic of analizing data use close coding and open coding. The results in this study explain that almost all Business Communication Strategies are effective in increasing customer satisfaction at Grand Tarakan Mall by looking at the 7 aspects of the Communication Strategy Pillar implemented by the Grand Tarakan Mall running even though it is not optimal because of the Declining phase that researchers see from PLC Theory.